Enhanced mechanical performance via laser induced nanostructure formation in an additively manufactured lightweight aluminum alloy. (March 2021) - Martin, Aiden A.; Hammons, Joshua A.; Henderson, Hunter B.; Calta, Nicholas P.; Nielsen, Michael H.; Cook, Caitlyn C.; Ye, Jianchao; Maich, Alyssa A.; Teslich, Nicholas E.; Li, Tian T.; Thompson, Michael J.; Besser, Matthew F.; et al.
Highlights: In situ X-ray diagnostics resolved laser-induced dynamics in AlCeMg. Ce-rich intermetallic phases within the melt pool form a fine nanostructure. Formed nanostructure is resistant to coarsening at elevated temperatures (300 °C). Tensile strength of additively manufactured components is superior to cast alloy. Material can be used for critical applications not typically suited to Al alloys. Abstract: To date, the primary focus of metal additive manufacturing (AM) research has been the development of strategies for fabricating complex architectures, reducing internal stress and optimizing microstructure. Traditional Al alloys have presented further challenges in this effort due to solidification cracking and complex laser coupling dynamics. To overcome these limitations, identification of novel alloys that exploit the rapid solidification conditions inherent in laser-based AM is required. In this work, laser-induced melting of an Al-8Ce-10Mg alloy is revealed to generate a nanoscale microstructure which results in improved hardness, tensile strength, and mitigated solidification cracking (e.g., hot tearing) in single laser tracks in as-cast material and laser powder bed fusion (LPBF)-fabricated components. In situ X-ray imaging shows the nanostructure arises from laser-induced melting of intermetallic particles embedded into the alloy during casting and then rapid resolidification of the molten material in 400 µs. The formed Ce-rich nanostructures are highly resistant to thermal coarsening at 300 °C, as confirmed by microscopy and retention of tensile properties. These results pave the way for development of AM-specific Al alloys that possess the ability to form mechanically favorable nanostructures in fabricated components due to the rapid cooling inherent in LPBF. Graphical abstract: Image, graphical abstract